The Influence of Supply Chain Management Practices on MSME Performance Using Methods SEM (Structural Equation Modeling) - Maharani, Dara Sekar; Mulandari, Yeni Sari; Mahatmayana, I Ketut Manu (Agribusiness Journal, 2024)
Gunungputri Village has great potential with a high number of entrepreneurs as a means of livelihood. Therefore, MSME players need to pay attention to the role of supply chain management practices which is very important to improve the performance of MSMEs. This research aims to analyze the partial and simultaneous influence of supply chain management practices on the performance of MSMEs. The data collection method uses a questionnaire. The sample and respondents were 145 processed food MSMEs. The analysis method uses Structural Equation Modeling (SEM), Smart PLS 4. The results of this study show that the partial influence of supply chain management practices on MSME performance is that only supplier relationship strategies, information sharing and warehouse management have a positive and significant effect on MSME performance. Meanwhile, consumer relationship strategies, information quality, delays and forecasting do not influence MSME performance. The research results show that supply chain management practices have a simultaneous influence on the performance of MSMEs and that the variables of supply chain management practices together have a simultaneous influence of 44.9 per cent and are in the medium category.